Revitalizing the Komering Language through Indigenous Music and Video-Based Learning - Edi Riyanto; Cipto Budi Handoyo (CV FOUNDAE, 2026)
Regional languages are increasingly threatened by globalization and the dominance of national and international languages, creating an urgent need for innovative educational approaches that support language revitalization among younger generations. Although digital learning offers new opportunities for cultural preservation, limited studies have integrated indigenous music with video-based learning to promote regional language acquisition. This study developed and evaluated a culturally responsive video-based learning medium featuring an original Komering song to support the revitalization of the Komering language. Employing a research and development approach based on the 4D model (define, design, develop, and disseminate), the study involved expert validation followed by implementation with junior high school students through online learning. Data were collected using expert validation questionnaires and Komering language proficiency assessments. The resulting learning media, Komering Payu Gham Lestaghiko, integrates original song lyrics, bilingual subtitles, traditional music, and authentic cultural representations, including Komering traditional clothing and architecture. The implementation demonstrated meaningful improvements in students’ Komering language proficiency and increased engagement with local cultural content. These findings suggest that integrating indigenous music into video-based learning provides a promising approach for strengthening regional language learning while supporting cultural preservation in digitally mediated educational environments. Although the findings should be interpreted cautiously because of the single-group implementation design, this study offers a practical model for developing culturally responsive digital learning resources that contribute to indigenous language revitalization.